RASIONALITAS ALQURAN DALAM TAFSIR AN-NUR: STUDI PENAFSIRAN SURAH AL-NISÃ‚â€™ [4]: 1 - Razali, Muhammad Syahrial (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2016)
The Islamic scholars seems to impose the ?discriminative? standard over the exegesis sanad (chain of narrators), where they accepts it loosely without restricted requirements as applied in ?adîth sanad. It is basically caused by the character of Qur?an itself as revealed in Arabic language, which is naturally resulting in the domination of reasoning (?aql) in interpreting and explaining its meanings (rational exegesis). But the problem here is when some rationalists scholars easily refused the authentic ?adîth just because it is in contrary to their reasoning or principles, even though the ?adîth undoubtedly has a significant role in interpreting the Qur?an. This paper attempts to analyze the exegesis thought of Teungku Muhammad Hasbi as appeared in his book of tafsir named ?Tafsir An-Nur? through his explanation of the first verses of surah al-Nisâ?; and to know to what extend his thought was influenced by rationalists. By using an analytical method, this research found that the thought of Teungku Muhammad Hasbi was influenced by rationalist scholars in interpreting the Qur?an because of deep relationship established between him and them